Den faustiske maske: Om en iscenesætters indre teater - Kuhlmann, Annelis (Peripeti, 2021)
In »The Mask of Faust« Kuhlmann reflects on danish director Sam Besekows (1911-2001) staging of himself as an artist in his work. She shows how the director’s »masking« of himself as mythological figures create images that on the one hand serves as sources of inspiration for the actors, and on the other hand unveils the specific professional identity of the director.